Exploring Socio-Economics and Its Role in the Oral Health Care of Patients in A Philippine Government Hospital - Alas, Carmi Angeline; Candelaria, Emilio Paul; Canlas, Jocelyn; Patacsil, Jaya Grace; Malang, Bernandino P. (Future Science / FSH-PH Publications, 2023)
Despite the availability of dental services and educational programs, as well as, established national health system responses, and oral health interventions and procedures, oral health problems (dental caries, gum diseases and unmet dental needs) persist in the Philippines. The aim of this study was to investigate the socioeconomic factors in terms of sex, age, marital status, educational attainment, occupation, and monthly income and their effect on the oral health awareness in terms of benefit and practices. A total of 100 patients from a selected government hospital were surveyed. The respondents were asked to answer a standardized questionnaire about their socioeconomic status, awareness on the benefits of oral health care, and awareness on the practices for oral health care. Chi-Square Test for Independence was used to identify which demographic and socioeconomic indicators determined the level of awareness of the respondents on the benefits of and practices for good oral health. The Chi-Square Test showed that only sex had a significant relationship with the awareness on the benefits of good oral health (p-value = 0.05). All the other indicators had insignificant effects; Age group (p-value = 0.435), Civil Status (p-value = 0.443), Education (p-value = 0.244), Employment status (p-value = 0.722), Income (p-value = 0.986). For the awareness on good oral practice, both sex and civil status showed a significant relationship (p-values 0.028 and 0.01). For the other indicators, null hypothesis was accepted; Age group (p-value = 0.61), education (p-value = 0.914), employment status (p-value = 0.334), income (p-value = 0.64). The results of this study are in line with the Andersen Healthcare Utilization Model, which holds that people's use of healthcare services is influenced by several predisposing, enabling, and need-related factors. The knowledge of, and observance of, good oral health is essential in determining the need for oral healthcare. Moreover, a variety of socioeconomic and personal factors (enabling and predisposing) are crucial in facilitating or impeding people's ability to access and make use of oral healthcare services. Addressing these issues and promoting education and knowledge about the value of excellent oral health practices are crucial for good oral health.